The Sin of Jesus Based on a Story by Isaac Babel - Babel', Isaak (Steidl, 2008)
A simple, fairly attractive woman named Arina works on a chicken farm, day after day. She looks forward to her man Felix coming home, but when he does he says he's going away, he can't stand their life anymore. Arina prays to Jesus in the barn to alleviate her loneliness, so Jesus appears with a gift. Jesus gives her a young angel named Alfred to be her husband, but she must always remember to remove his wings at night or else he will die. Angels come to celebrate the happy wedding. That night in passion Arina mounts Alfred for sex while his wings are still on. Alfred dies, and Jesus condemns Arina. But she protests that it was God who made her to be lustful and stupid, so Jesus begs her forgiveness ... [www.astralresearch.org]
Keywords: DVD-Video